Tinjauan Sistematis Tentang Integrasi Keuangan Digital dalam Pasar Keuangan Syariah: Risiko dan Tantangan - Dzil Jalal, A M Fadli; Rosyadi, Imron; Syamsul Hidayat (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to identify and analyze the challenges and risks faced in the integration of digital finance in the Islamic financial market. The phenomena studied focus on regulatory uncertainty, limited digital infrastructure, and the difficulty of ensuring sharia compliance in the development of Islamic fintech products. The research approach used is the Systematic Literature Review (SLR) by following the PRISMA protocol to ensure the accuracy of literature selection. Data were collected from the Scopus and Web of Science databases, with publication criteria in the last eight years (2017–2025). A total of 23 selected articles were analyzed using thematic and narrative techniques. The results of the study indicate that the main challenges in the development of Islamic digital finance include regulatory asynchronous, limited public literacy, digital infrastructure gaps, and limited DPS (Sharia Supervisory Board) competence in technology supervision. The identified risks include the risk of sharia non-compliance, the risk of losing market trust, data security risks, and the risk of innovation stagnation due to delays in technology adaptation.